Development of High-Q Sensor for NQR Detection of Dangerous Materials - Mamadazizov, Sultonazar; Calicioglu, N. Gazale; Ryzhov, Rian; Mozzhukhin, Georgy; Rameev, Bulat (IEEE, 2022)
Nuclear Quadrupole Resonance (NQR) is a conventional technique for solid sample investigation. However,one of the main disadvantages of NQR is the low signal-to-noise ratio at low frequencies. This could be resolved by designing high sensitive coils. The goal of the current work is to develop an RF probe with a high quality factor. Thus, a finite element modelingsimulation of several planar RF coil configurations using the CST Studio package was made.
Photonics and Electromagnetics Research Symposium (PIERS) -- APR 25-27, 2022 -- Hangzhou, PEOPLES R CHINA
Keywords: Resonance